Beyond Infection: The Role of Secreted Viral Proteins in Pathogenesis, Disease Severity and Diagnostic Applications - Luis Herrera-Moro Huitron; Víctor Javier Cruz-Holguin; José Manuel Ulloa-Aguilar; Luis Adrián De Jesús-González; Juan Fidel Osuna-Ramos; Mario Guzmán-Huerta; Mercedes Piedad de León-Bautista; Guadalupe León-Reyes; Julio García-Cordero; Leticia Cedillo-Barrón; Jorge Francisco Cerna-Cortes; Moisés León-Juárez (Cells)
Secreted viral proteins are crucial in virus–host interactions, as they modify the host microenvironment to promote infection. These secreted proteins could alter immune and inflammatory responses, allowing viruses to evade defense mechanisms such as cytotoxic T cell activation and antibody neutralization. Some secreted proteins mimic host molecules to suppress antiviral responses, making them valuable targets for antivirals and diagnostics. Notable examples include BARF1 from Epstein–Barr virus, associated with gastric cancer; vIL-10 from Epstein–Barr virus, which regulates immune responses and contributes to autoimmune diseases; NS1 from dengue virus, associated with vascular permeability and early diagnosis; and NSP4 from rotavirus as an enterotoxin, among others. The study of these proteins improves our understanding of viral pathogenesis and helps to develop innovative treatments for infectious and non-infectious diseases, taking advantage of the evolutionary adaptations of viruses. This review explores their impact on the infection cycle, disease progression, and key processes, such as cell cycle regulation, apoptosis, and cell signaling. Research on these proteins deepens our basic knowledge of virology and generates alternative methods for detecting biomarkers and creating more effective therapies, as well as implementing some emerging technologies, such as biosensors and plasmon resonance, for the diagnosis of viral diseases.